2023
DOI: 10.2196/38528
|View full text |Cite
|
Sign up to set email alerts
|

Using a Designathon to Develop an HIV Self-Testing Intervention to Improve Linkage to Care Among Youths in Nigeria: Qualitative Approach Based on a Participatory Research Action Framework

Abstract: Background UNAIDS (Joint United Nations Programme on HIV and AIDS) and the Nigeria National HIV/AIDS Strategic Framework recommend HIV self-testing and youth-friendly services to enhance HIV testing, linkage to health services, and prevention. However, the voices of youths are seldom incorporated into interventions. We examined qualitative data generated from a series of participatory events in partnership with Nigerian youths focused on enhancing linkage to care. … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
13
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(14 citation statements)
references
References 33 publications
1
13
0
Order By: Relevance
“…We retrieved 127 publications from additional searches (ie, citation searching and the complementary open call), with a further 11 publications included in this review. In total, we included 42 studies in this review,7 8 18–57 with 39 studies (93%) focusing on developing social innovations 7 8 18–20 22–42 44–53 55–57. The PRISMA flowchart is presented in online supplemental figure 1.…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…We retrieved 127 publications from additional searches (ie, citation searching and the complementary open call), with a further 11 publications included in this review. In total, we included 42 studies in this review,7 8 18–57 with 39 studies (93%) focusing on developing social innovations 7 8 18–20 22–42 44–53 55–57. The PRISMA flowchart is presented in online supplemental figure 1.…”
Section: Resultsmentioning
confidence: 99%
“…In total, 41 studies (98%) reported the number of designathon participants 7 8 18–53 55–57. The median number of individuals participating in designathons was 49 (IQR 34–90, range 6–434), and the median number of teams was 8 (IQR 5–14.5, range 2–40).…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations